Design and Development of E-Prescription System - Mr. Dilip R, Bharath N, Kushal Dayananda K, Lokananda Karunakar, Sherin Varghese (International Journal of Advanced Science and Technology, 2020)
Most of the people in the daily life looks for their nearby hospitals to get to know about their health condition. By the proposed model of health monitoring systems an individual or person can get to know about his or her health parameters such as Heart Rate, ECG and Body Temperature in a single device. Here the human body parameters are fetched by the bio sensors, the collected data are forwarded to the controlling unit for further processing of the data. Once the gathered parameters are compared against the required body parameters, if there is any changes it will look up for the required particular medicine in the database then the prescription along with the medicine will be sent to the patient phone number as a message. Index Terms: Raspberry Pi 4, ECG sensor, pulse rate sensor, Temperature sensor, RFID ThingSpeak Cloud, Mongodb